2017
DOI: 10.1111/tid.12777
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to listing for HIV‐infected patients being evaluated for kidney transplantation

Abstract: Background Human immunodeficiency virus (HIV)-infected patients have excellent outcomes following kidney transplantation (KT) but still might face barriers in the evaluation and listing process. The aim of this study was to characterize the patient population, referral patterns, and outcomes of HIV-infected patients who present for KT evaluation. Methods We performed a single-center retrospective cohort study of HIV-infected patients who were evaluated for KT. The primary outcome was time to determination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…HIV+ candidates face numerous barriers to transplantation. They are subject to a more intensive evaluation process that often prolongs their time to waitlisting . Not all transplant centers will accept them as candidates, although the number of transplants performed in HIV+ recipients at centers that did not participate in the original NIH multicenter trial has grown .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV+ candidates face numerous barriers to transplantation. They are subject to a more intensive evaluation process that often prolongs their time to waitlisting . Not all transplant centers will accept them as candidates, although the number of transplants performed in HIV+ recipients at centers that did not participate in the original NIH multicenter trial has grown .…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that only 30% of HIV+ candidates referred for transplantation at a single center were ultimately listed, compared to 73% of their HIV negative (HIV‐) contemporaries . A more recent analysis reported improved rates of listing (70%) but 22.6% of candidates were unable to complete all of the testing required for listing and 50% of those ultimately listed for transplant experienced delays in navigating the evaluation process . Unfortunately, waitlisting alone does not guarantee transplant access for HIV+ patients.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main differences was HCV coinfection, which was more frequent among PLHIV. Previous studies showed that active drug use, psychosocial difficulties, and medical insurance issues act as barriers to waiting list enrollment of PLHIV, 31,32 and HCV coinfection could be considered as a proxy for these characteristics. However, when the analyses were performed on the subgroup of patients without HCV, both the access to the WL and to KT remained severely compromised for PLHIV compared to HIV-uninfected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that active drug use, psychosocial difficulties, and medical insurance issues act as barriers to waiting list enrollment of PLHIV,31,32 and HCV coinfection could be considered as a proxy for these characteristics. PLHIV and controls showed relatively similar comorbidities.…”
mentioning
confidence: 99%
“…Timely referral for kidney transplantation is crucial for HIV-positive transplant candidates because their transplant evaluation process is lengthier and more complex. In addition to the standard evaluation performed by the nephrologist and surgeon, which includes cardiac risk stratification and general health maintenance screenings, HIV-positive candidates require a careful assessment of their social support and substance abuse history; active substance abuse issues are a common reason HIV-positive candidates fail to achieve waitlisting (2). Additionally, as many are coinfected with hepatitis C (HCV) or hepatitis B, evaluation by a hepatologist is often necessary.…”
Section: Which Hiv-positive Patients Are Appropriate For Kidney Transmentioning
confidence: 99%